Pembangunan Berkelanjutan di Pesisir Indonesia: Tantangan dan Solusi atas Ancaman Lingkungan - Perdani, Agung Sandi; Umar, Genius; Dewata, Indang; Amar, Syamsul (PT Hakhara Akademia Indonesia, 2025)
Indonesia's coastal areas hold great potential in terms of economy, ecology, and social. However, unplanned development and excessive exploitation of resources have caused serious environmental damage, such as pollution, abrasion, and degradation of mangrove and coral reef ecosystems. This article discusses the main forms and causes of coastal environmental damage and outlines effective strategies and solutions in realizing sustainable development. The approach used is integrated and participatory, with an emphasis on the importance of synergy between sectors, community involvement, ecosystem conservation, regulatory enforcement, and the implementation of the blue economy. The results of the discussion show that the success of coastal development depends on cross-party collaboration and consistent implementation of sustainable principles. The obligation of long-term commitment so that development is not only beneficial for the current generation but also ensures commitment to future generations.